2022
DOI: 10.1371/journal.pgph.0000072
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the availability and affordability of essential cardiovascular disease medicines in low- and middle-income countries: A systematic review

Abstract: Despite their potential to prevent or delay the onset and progression of cardiovascular disease (CVD), medicines for CVD remain unavailable and unaffordable to many in low- and middle-income countries (LMICs). We systematically reviewed the literature to identify factors associated with availability and affordability of CVD medicines in LMICs. A protocol for this study was registered on the PROSPERO register of systematic reviews (CRD42019135393). We searched Medline, EMBASE, Global Health, Cumulative Index to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Measurements of affordability, for example, were performed with different methods. A review of availability and affordability of CV medicines by Lotfizadeh et al showed similar findings [ 43 ].…”
Section: Discussionmentioning
confidence: 67%
“…Measurements of affordability, for example, were performed with different methods. A review of availability and affordability of CV medicines by Lotfizadeh et al showed similar findings [ 43 ].…”
Section: Discussionmentioning
confidence: 67%
“…In Kenya, for example, the prevalence of hypertension among people aged 18–69 years is estimated at 24.5% (2), and only 3% of those diagnosed have their blood pressure controlled (3). This gap in treatment has been attributed to inconsistent availability and affordability of antihypertensives (4), poor adherence to prescribed treatment, (5) the high number and diversity of anti-hypertensive medication treatment options, which can make treatment complex (6), and ‘therapeutic inertia’, or the failure of physicians to initiate or intensify therapy when BP remains elevated (7). Despite evidence that 75-80% of hypertensive patients require multiple classes of drugs to effectively control their blood pressure, many receive monotherapy (one drug) (8).…”
Section: Introductionmentioning
confidence: 99%